Legal Problems and Agamben‘s "State of Emergency" in Post-February Russia: Methodological Analysis - Kuksa, Tatiana; Fedosova, Ksenia (Տիգրան Մեծ)
This article presents document flow in the context of the “state of exception” (according to Giorgio Agamben), which abolishes the effect of the usual legal distinctions, when, for example, “it is impossible to draw a line between peace and war”. As a scientific contribution, the authors deepen the binary/bipolar dimension of complaints/ denunciations to a plural and bureaucratic dimension and explore them from a plurality of perspectives: user, legislative and law enforcement.The statistics indicates that the vast majority of investigations are related to the anti-war Internet activity of the defendants, for registration and evidence of which predominantly automated search systems and screen-work by law enforcement bureaucrats are used, rather than a written or oral flow of grassroots/spontaneous complaints/ denunciations. Research shows the diversity of government agencies/bodies involved and interdepartmental competition for quick quantitative results (the ratio of cases filed and sentences), as well as Agamben’s abolition of customary legal distinctions.
Keywords: Denunciation